Digitalisasi dan Tantangan Moral: Strategi Guru PAI di SDN PasirBaru dalam Membentuk Karakter Siswa - Neng Suci; Acip; Solahudin (Prodi Pendidikan Agama Islam, IAIN Sultan Amai Gorontalo, 2025)
Digitalization has brought a significant impact on education, particularly in shaping the character of elementary school students. Islamic Education (PAI) teachers face moral challenges arising from the uncontrolled use of digital media. This study aims to explore the strategies employed by PAI teachers at SDN PasirBaru in fostering students’ character amid the wave of digitalization. The research applies a literature review method with thematic analysis of relevant national and international studies published between 2014 and 2024. The findings reveal that several effective strategies can be implemented, namely: (1) integrating Islamic values into students’ digital lives, (2) utilizing appropriate character-based learning media, (3) teachers’ role modeling as behavioral exemplars, and (4) close collaboration with parents in monitoring technology use. These strategies are proven relevant in addressing moral challenges in the digital era, particularly in preventing value degradation and deviant behavior among elementary students.The implications of this study highlight the urgency of strengthening digital literacy among PAI teachers, developing contextual Islamic character education models, and fostering collaborative support between schools, families, and policymakers. Thus, this research provides both theoretical contributions to enrich the discourse on character education in the digital era and practical guidance for teachers and schools in shaping religious and virtuous young generations.